Meloxicam as a Radiation-Protective Agent on Mandibles of Irradiated Rats - Yamasaki,Mayra Cristina (2017)
Abstract This study evaluated the action of ionizing radiation and the possible radioprotective effect of the non-steroidal anti-inflammatory drug meloxicam on the bone physiology of rat mandibles by assessing the alveolar socket healing and bone strength. Forty male Wistar rats were divided in 4 groups (n=10): control (CG), irradiated (IG), meloxicam (MG), meloxicam irradiated (MIG). A dose of 0.2 mg/kg meloxicam was administered to MG and MIG. After this, IG and MIG were irradiated with 15 Gy radiation dose in the mandible. Forty days after the above procedures, the mandibular first molars were extracted and the animals were killed after 15 or 30 days (n=5). Micro-computed tomography and bending test were used to evaluate alveolar socket healing and bone strength, respectively. At 15 days, bone volume, bone volume fraction and trabecular thickness were higher in the CG and MG than in the IG and MIG; and trabecular separation was higher in the IG compared with the others. At 30 days, there was a difference only in trabecular separation, which was higher in IG than in CG and MG, and MIG did not differ from the others. Bone strength was lower in IG compared with CG and MG, and MIG did not differ from the others. In conclusion, the ionizing radiation affected the bone physiology of rat mandibles, delaying the alveolar socket healing and reducing the bone strength. Moreover, the meloxicam had a positive effect on the trabecular separation in alveolar socket healing and on the bone strength.